Geography education in perspective: an enquiry into Ghanaian senior high school students' positive and negative attitudes towards geography. Issue 1 (2nd January 2021) - Opoku, Foster; Serbeh, Richard; Amoah, Ebenezer Gyampoh
Abstract: This paper examines the factors accounting for students' predilection or aversion for school Geography. The paper draws on data from 116 students (aged 14–19 years) sampled from three public Senior High Schools (SHSs) in the Offinso Municipality of the Asante Region, Ghana. We employed the a posteriori inductive reduction model to derive broad and interlinking themes from the individual interviews conducted with study participants. In consonance with the cognitive interest and expectancy-value theoretical perspectives, we found that the multi-textured nature of Geography, which produces holistic knowledge for addressing individual and societal problems and more importantly lending itself to diverse job opportunities, constituted the major pull factors explaining students' positive attitudes towards Geography. Contrariwise, perceived subject difficulty and poor performance resulting from inadequate outdoor experiential Geography vis-a-vis poor teaching methodologies and the societal notion of geography not being prestigious or lucrative enough constituted the push factors underlying students' aversion for the subject. The findings suggest making outdoor practical lessons compulsory component of Geography education in order to offer students the opportunity to relate concepts to real world situations.